Guadalupe Victoria correspondence - Victoria, Guadalupe, 1786-1843.
ALS written by Victoria indicating to Spanish colonial authorities Mexican approval of negotiations with them.
Army officer elected president of Mexico in 1824. Original name: Manuel Felix Fernandez; changed name to show devotion to Mexican independence.
Collection material in Spanish.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Mexico -- History -- 1821-1861.; New Spain -- History; Army officers, Mexican; Presidents -- Mexico